The Influence of Doses Manure Chicken Against The Growth and The Production of The Green Buncis (Phaseolus Vulgaris L) - Wa Ode Anti; La Ode Hidayat; Samiati Samiati; Muh Rufendi (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
This study aims to: (a) determine the effect of chicken manure dose on the growth and production of green beans, and (b) determine what dose of chicken manure gives the best growth and production of chickpeas. This research was conducted in Lamorende Village, Tongkuno District, Muna Regency starting from September to November 2020. This research was arranged based on a randomized block design (RBD) with one factor, which consisted of four (4) levels of treatment, namely without chicken manure (A0), manure. chicken with a dose of 10 t ha-1 or 2.4 kg plot-1 (A1), chicken manure at a dose of 20 t ha-1 or 3.6 kg plot-1 (A2), and chicken manure at a dose of 30 t ha- 1 or 4.8 kg plot-1 (A3). Data from the observations of each parameter were analyzed using Analysis of Variance (ANOVA). The results showed that the treatment of chicken manure dose had a very significant effect on plant height, number of leaves, pod weight per plant, number of pods per plant, and bean production. Manure at a dose of 30 t ha-1, gave better growth and production of beans, with a production of 9.83 g plant-1.